History below the global : on and beyond the coloniality of power in historical research - Kamel, Lorenzo, 1980- (Abingdon, Oxon ; New York, NY : Routledge, 2024)
"History Below the Global aims to foster an entangled knowledge of global history, and to place 'others' at the centre stage, to better understand the fluid world which we inhabit. Relying on primary sources in seven languages and books written by hundreds of African, Asian, Middle Eastern and South American scholars, Lorenzo Kamel examines the coloniality of power in historical research and sheds light on the largely neglected roles of the 'others' and their modernities in history. The book provides three elements combined. Firstly, a thorough analysis of the process of accumulation ("knowledge piece by piece") which underpins some of major achievements in human history. Secondly, a view on pre-colonial perspectives and the process through which the latter have been swallowed up by Eurocentric and solipsistic perceptions. Lastly, a study on the roots and outcomes of colonialisms and their echoes on our present. These three elements are addressed by combining multiple methodologies and approaches, in the awareness that the history analysed, as well as the historiographical trajectories that underlie it, are ultimately inter-penetrable, as well as themselves the result of a process of accumulation. History Below the Global challenges the view that, first and foremost, the "West", for bad and for good, is and was the centre: the proactive actor which did and undid. This volume will be of value to all those interested in global history, the history of colonialism, post-colonial studies, modern and contemporary history"--
Unlearning -- The man of his time -- Enslaved and 'civilized' people -- Colonialism's new faces -- Decolonization : from Third World to Global South -- The Middle East, beyond "artificial states" -- A revolution "against global systems" -- Conclusion. Fostering discordant facts.
Keywords: History -- Methodology; History -- Research; World history -- Historiography; Imperialism -- Historiography; HISTORY / World; HISTORY / Modern / General; HISTORY / Historiography